Determination of bisphenol a in plastic packaging by uv-vis spectrophotometric method - Yudin, Noor Shazwani Anu Ar Maha (Universiti Sains Malaysia, 2017)
Bisphenol A (BPA) is a widely used chemical in the plastic production and it is well known as weak estrogenic character which can give potential endocrine disruptor to human body. In this study, trace amounts of BPA have been detected in five different type and brands of plastic packaging sample purchased from a local supermarkets. The concentration of BPA leaching at different temperature was measured using a simple, sensitive and rapid UV-Vis spectrophotometric method. The detector wavelength was set at 276 run. Linear standard curve was obtained over the range from 0.07 to 0.35 mM with regression coefficient of 0.992 and detection limit of 0.0002 mM. Based on the result, brand 1 of HM type has the lowest concentration of BPA leach out from sample when it immersed in 0 °C with the detection of 1.148 x 10'7± 0.236 x 10"3 g/cm2, while HD type sample has the highest value of concentration of BPA leaching with measurement value of 6.861 x 10‘7 ± 2.915 x 10'3 g/cm2 when it immersed in 70 °C. Although the concentration of BPA leached out from all types of plastic sample in every different temperature were detected, though as the part of research concern, it is still safe to use because all the values of concentration BPA detected in this study was still under the NOAEL range (5 mg/kg bw/day).